STRATEGIES OF ELECTRIC BUS IMPLEMENTATION IN SOEKARNO-HATTA AIRPORT USING STRENGTH-WEAKNESS-OPPORTUNITY-THREAT (SWOT) ANALYSIS AND QUANTITATIVE STRATEGIC PROGRAMMING MATRIX - Rahman, Andhika; Kuntjoro, Yanif Dwi; Supriyadi, Imam (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
Most of the transportation in Indonesia still uses oil as their fuel, thus Indonesia is currently facing one of the Energy Security issues which are oil availability. Nowadays, Indonesia doesnâ€™t have sufficient oil production, consequently, Indonesia must import oil to meet its daily demand. Furthermore, Indonesia also dealing with an environmental issue from the transportation sector, which is air pollution. Air pollution is one of the non-military threats that threaten the lives of many people in Indonesia. The non-military defense is an effort made to ward off non-military threats. One of the ways to fight air pollution is to reduce the use of oil in the transportation sector.Â Currently, the development of innovative technology in the field of transportation is increasingly oriented to electric vehicles (EV). This is due to EVs that do not produce gas emissions, increase energy efficiency, and reduce oil consumption. In August 2018, a one-week trial runs on an electric bus at Soekarno-Hatta Airport conducted to looking for responses from passengers when boarding an electric bus as an airport shuttle bus. Therefore, this study will be further determining the strategies of electric bus implementation at Soekarno-Hatta Airport. The method used is a qualitative method using a case study approach and Strength-Weakness-Opportunity-Threat Analysis with Quantitative Strategic Programming Matrix. This study concludes that the strategy that has to be implemented first for electric bus implementation in Soekarno-Hatta Airport is Strength-Opportunity 3 (SO3) strategy, which is collaborating with Bus Companies to become a pioneer in electric bus implementation in Indonesiaâ€™s Airport and improve the Eco Airports Status.